2014
DOI: 10.1111/bjc.12042
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation schema responds to positive social experiences: Longitudinal evidence from vulnerable populations

Abstract: Maladaptive schemas are modifiable in short-term therapy or even in community settings. The experience of being accepted and belonging to a social group can challenge a person's deep-seated belief that they are socially isolated. Positive social experiences may act as scaffolding to help socially isolated individuals build new social group memberships. Less positively, social isolation schema can also act as a feedback loop, preventing people from identifying with groups, resulting in a negative social experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…Indeed, participants who continued to identify with their substance using peers at follow‐up were experiencing much poorer outcomes across all measures of substance use and life satisfaction, while those who maintained their recovery social identity showed positive outcomes on substance use and life satisfaction. This provides an important caveat to the ‘groups are good for you’ message of the social cure tradition (Jetten et al ., ), suggesting that the scope of such effects are limited to those groups that do not have norms for behaviours that are maladaptive for health (see also Cruwys, Dingle, et al ., ; Cruwys, Haslam, et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, participants who continued to identify with their substance using peers at follow‐up were experiencing much poorer outcomes across all measures of substance use and life satisfaction, while those who maintained their recovery social identity showed positive outcomes on substance use and life satisfaction. This provides an important caveat to the ‘groups are good for you’ message of the social cure tradition (Jetten et al ., ), suggesting that the scope of such effects are limited to those groups that do not have norms for behaviours that are maladaptive for health (see also Cruwys, Dingle, et al ., ; Cruwys, Haslam, et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly for our analysis, evidence has suggested that internalizing groups in this way has substantial benefits for health and well‐being, because groups provide us with a sense of belonging, meaning, and purpose, as well as enabling material benefits such as social support (Haslam, Jetten, Postmes, & Haslam, ). For example, people experiencing mental health problems benefit greatly from joining meaningful social groups – including both therapy groups and other community groups such as choirs, sporting, and cultural groups (Cruwys, Dingle, Haslam, et al ., ; Cruwys, Dingle, Hornsey, et al ., ; Dingle, Brander, Ballantyne, & Baker, ). Social identities have also been found to improve health and well‐being for individuals with multiple sclerosis (Wakefield, Bickley, & Sani, ), post‐traumatic stress (Jones et al ., ), and physical disabilities (Fernández, Branscombe, Gómez, & Morales, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, service use has consistently been associated with better mental health outcomes among those experiencing homelessness (Gabrielan et al, 2015; Small, 2010). Given that mental health problems are strongly connected to social isolation and loneliness, especially among those experiencing homelessness (Cruwys et al, 2014; Hodgson et al, 2015), service connection might mediate cumulative risk and mental health status by reducing loneliness and social isolation. Alternatively, services might have imparted other benefits to mental health such as skills acquisition, and access to medication, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness, the subjective experience of unmet social and emotional needs associated with social isolation (Perese & Wolf, ), is viewed as a major problem for people with psychiatric disabilities living in the community (Davidson et al., ; Green, Wisdom, Wolfe, & Firemark, ; Yanos, Felton, Tsemberis, & Frye, ). While independent living promotes autonomy and economic viability, isolation and loneliness may endure over time (Bartels & Pratt, ; Cruwys, Dingle, et al., ; Siegel et al., ).…”
Section: Introductionmentioning
confidence: 99%